DEVELOPMENT OF TEACHING MATERIALS ON 7 OBJECTS OF THINGS, ANIMALS AND PLANTS AROUND ME WITH SUB-THEME 3 OF LIVING THINGS AT CLASS 1 ELEMENTARY STUDENTS BASED ON SCIENTIFIC - Evi Rohmawati; Muhammad Ilyas; Ventje J Kalukar (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
This study aims to find out whether there are differences in learning outcomes of grade 1 elementary school students who use learning supplement books developed in the sub-theme 1 Living Objects Around me with learning outcomes of students who do not use learning supplement books developed in the sub-themes of 1 Living Objects Around Me. use research and development methods. The research and development procedure used is a modification of the Borg and Gall development model which includes seven steps of development namely stage (1) research and information gathering; (2) planning; (3) development of preliminary product forms; (4) preliminary trials; (5) revisions to the main products; (6) the main trial based on the results of the preliminary trial; (7) revision of operational products; (8) trial. operational; (9) final product revisions; and (10) dissemination and implementation. until it becomes the final product of teaching materials that refers to the 2013 curriculum. Theme 7 Objects, Animals and Plants Around Me subtema 1 Living Objects for class 1 Elementary School. Development of teaching materials using instruments that are interviews, observations, discussions with experts, competency tests, questionnaires, likert scales that are made in the form of a checklist such as questionnaires for expert validation. The technical data analysis used in this study is qualitative and quantitative data. The results of this study are teaching materials that refer to the 2013 curriculum sub-theme 1 Living Objects for grade 1 elementary school. Before and after the supplement book can be seen from the difference in the average pre-test and post-test that is 68.6 and 87.8 Feasibility Evaluation of Thematic Learning by using Rubrics with 3 material expert Validator Tests of 96%, madia expert Validator Test 89% of education expert Validator tests were 93.3%. Evaluation of supplementary book learning with a small group trial of 89.5%, and a large group test of 93.7%.